Optimasi Parameter Tekanan pada Penumbuhan Lapisan Tipis Silikon Amorf Terhidrogenasi dengan Sistem Hot Wire PECVD - Syamsu Syamsu; Amiruddin Kade; Haeruddin Haeruddin (Media Eksakta, 2014)
The HW-PECVD system was then applied to grow a-Si:H thin films on corning glass 7059 by using 10% silane (SiH4) gas diluted in hydrogen (H2) as gas source. By optimization of deposition presure, a better quality a-Si:H thin films with dark conductivities is relative high (4.23x10-9 S/cm). The deposition rate and the optical band gap of the a-Si:H thin film were 0.68 Å/s and 1.98 eV. These results showed that by using HW-PECVD system, the optical properties was successfully increased without deteriorating in the electrical properties.